Pelaksanaan Aktivitas Keagamaan dalam Rangka Optimalisasi Kehidupan Beragama Warga Sekolah di SMA Negeri 2 Sembawa Kabupaten Banyuasin - Mulyadi Mulyadi (Journal on Education, 2023)
Education is an investment in civilization that is very necessary in an effort to produce quality human resources. Quality education is education that can form a civilized person so as to create a social life with character. The focus of this research is on the implementation of religious activities, namely: reading verses of the Qur'an or tadarus, dhuha prayers, congregational midday prayers, tausiyah or speeches and commemoration of Islamic holy days (PHBI) religious activities in SMA Negeri 2 Sembawa Banyuasin Regency. The type of data used in this study is a type of qualitative data. This study uses data sources consisting of two kinds of data sources, namely primary and secondary data sources. Data collection techniques in this research are observation, interviews, documentation. While the data analysis technique used in this research is descriptive data analysis technique with the type of data in the form of information, both spoken and written, which are not numbers in nature. The results of this study show that the activities of implementing religious activities for students at SMA Negeri 2 Sembawa, Banyuasin Regency are effective. This is based on the criteria for implementing religious activities, providing adequate facilities and infrastructure, improving the quality of activities, quality and leadership style of democratic educational institutions and professional and good teamwork.